Application of ι-Carragenan/Agarose Hydrogel as Super Adsorbent Hydrophilic Polymers Natural Seed Coating for Improving Tobacco Seed Germination Under Drought Stress - Arum, Ayu Puspita; Setiyono (Future Science, 2023)
Seed storage for a long time causes seed deterioration. Reduction of germination rate can cause abnormal growth of the seedling, which impacts the yield and quality of tobacco plants. Seed coating is an additive that coats the seeds with certain ingredients such as pesticides, and nutrients that are glued to a binding material for improved seed performance without changing its origin's form. Hydrogel seed coating is also natural and environmentally friendly which is suitable for organic and sustainable farming practices. In countries with worse droughts and depending on natural plants, natural seed coating using agarose and Carragenan is very well applied. Carrageenans regulate many of the metabolic pathways involved in nitrogen and sulfur absorption, making it easier to grow plants by regulating a variety of metabolism processes including photosynthesis as well as an ancillary pathway. In conditions of drought stress, salicylic acid treatment may have a beneficial effect on plant resistance. In plants, salicylic acid regulates the growth of endogenous cells and plays an important role in abiotic stress signal transduction. The present field experiment was conducted to evaluate the effectiveness of ι-Carragenan/Agarose hydrogel as super adsorbent hydrophilic polymers natural seed coating with 3 type combination of ι-Carragenan and Agarose (1:1; 1:2 and 2:1)% w/w containing salicylic acid 0.15% w/w to improve sprouting speed index, sprouting percentage, fresh seed mass and seed vigor index of tobacco seeds which are 3 variety storage time (13 years, 9 years and 3 years) under drought stress condition (40% moisture levels). The results revealed that application of ratio ι-Carragenan/Agarose 1:2 and 2: 1 % w/w containing salicylic acid 0.15% w/w recommended of Super Adsorbent Hydrophilic polymers Natural Seed Coating formulation enhanced of sprouting speed index, germination percentage, and seed vigor index of 2 variety storage time of tobacco seed (13 years and 9 years).